PROBLEMS OF USING NEURAL NETWORKS TO PREDICT THE PRICE OF VIRTUAL ASSETS - Andrii Tsemko; Maxym Matskiv (Електроніка та інформаційні технології)
Background. Predicting the prices of virtual assets is an important task due to their high volatility. Neural networks are widely used for such tasks, but often face the problem of naive predictions, when the next value is too similar to the previous one, which reduces the forecasting efficiency.